1990
DOI: 10.1046/j.1537-2995.1990.30190117625.x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of white cells from red cells by transfusion through a new filter

Abstract: The effectiveness of a new filter (RC100) for the preparation of white cell-depleted red cells (RBCs) at the bedside was evaluated in vitro and in vivo using three RBC products: standard RBC concentrate (CPDA units), RBCs suspended in saline-adenine-glucose-mannitol additive solution after the removal of plasma (SAGM units), and RBCs suspended in SAGM after the removal of plasma and buffy coat (SAGM-BC units). Median RBC recovery was at least 92 percent when 2 units were administered through one filter; median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Leucocyte depletion decreases the incidence of adverse transfusion outcomes such as HLA alloimmunisation or febrile non-haemolytic reactions [3, 4, 5, 6]. Furthermore, pre-storage leucocyte depletion reduces supernatant levels of leucocyte enzymes [7, 8]and improves biochemical parameters of stored human red blood cells (RBCs) [1, 9, 10, 11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Leucocyte depletion decreases the incidence of adverse transfusion outcomes such as HLA alloimmunisation or febrile non-haemolytic reactions [3, 4, 5, 6]. Furthermore, pre-storage leucocyte depletion reduces supernatant levels of leucocyte enzymes [7, 8]and improves biochemical parameters of stored human red blood cells (RBCs) [1, 9, 10, 11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…The leukocyte filtration was performed bed-side, and the efficacy of bed-side filtration has been tested by different study groups [19]. There is now general agreement that prestorage filtration will give more standardized products, because the filtration will be carried out under standardized circumstances [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…The filtration was performed at the bed-side using PALL RC100 (Meda, Copenhagen, Denmark) for erythrocyte transfusion and PALL PL50 if platelets had to be transfused. The efficacy of the PALL RC100 filter has previously been investigated by Sirchia et al [19], which found < 20 × 10 6 leukocytes per litre after filtration. This is equivalent to a leukocyte reduction of 99.9%.…”
Section: Methodsmentioning
confidence: 99%
“…This concentration of LMWH allows the generation of thrombin when blood is exposed to a denuded vascular segment. [19][20][21][22] Blood platelets and leukocytes were reduced by a filtration procedure, 23 using an RC100 filter (PALL Corp, Glen Cove, NY). The platelet number was adjusted to 30,000 platelets/µL, mixing thrombocytopenic blood and whole blood.…”
Section: Blood Collection and Preparation Of Thrombocytopenic Bloodmentioning
confidence: 99%